2019
DOI: 10.1021/acsenergylett.9b02397
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Energetic Landscape of Ruddlesden–Popper Perovskite Films for Efficient Solar Cells

Abstract: Ruddlesden−Popper perovskite films deposited with different methods show very diverse phase segregation and composition. When DMSO is used as solvent, the conventional method based on spin-coating and annealing produces very poor devices, whereas the vacuum-assisted method proposed here allows obtaining devices with efficiency up to 14.14%. The conventional method gives rise to a three-dimensional (3D)-like phase on the top of the film but dominant n = 2 phase with large domains (∼40 μm) at the bottom of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 29 publications
1
76
0
Order By: Relevance
“…Thus, by performing the preparation process under vacuum conditions, the evaporation rate of the solvent can be changed, thereby affecting the crystallization process of the 2D perovskite. [141] The crystallization process of 2D perovskite is linked to the competition between the evaporation rate of the solvent and the growth rate of the seed crystal. [142] A low supersaturation is necessary to induce nucleation of perovskite at the gas-liquid interface and for it to grow perpendicular to the substrate (Figure 7c).…”
Section: Vacuum Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, by performing the preparation process under vacuum conditions, the evaporation rate of the solvent can be changed, thereby affecting the crystallization process of the 2D perovskite. [141] The crystallization process of 2D perovskite is linked to the competition between the evaporation rate of the solvent and the growth rate of the seed crystal. [142] A low supersaturation is necessary to induce nucleation of perovskite at the gas-liquid interface and for it to grow perpendicular to the substrate (Figure 7c).…”
Section: Vacuum Methodsmentioning
confidence: 99%
“…Thus, by performing the preparation process under vacuum conditions, the evaporation rate of the solvent can be changed, thereby affecting the crystallization process of the 2D perovskite. [ 141 ]…”
Section: Crystallization Kineticsmentioning
confidence: 99%
“…Zhou et al 18 also demonstrated that the <n> value distribution could be controlled by introducing methylammonium chloride additive. Subsequently, Shao et al 19 successfully tuned the energy landscape of perovskite films via a vacuum-assisted method. Reduced low <n> value components favorably promoted the carrier transport and effectively suppressed the charge recombination.…”
mentioning
confidence: 99%
“…Similarly, the vacuum‐assisted method allows 2D perovskite to be evenly distributed in the film, which helps to charge transfer and reduces the recombination. [ 141 ] Thus, this greatly reduces the hysteresis level. The difference from the R–P phase is that the spacer cations used in the D–J phase are divalent organic cations.…”
Section: Methods Of Reducing or Eliminating Hysteresismentioning
confidence: 99%